Kontribusi Indonesia dalam Peacekeeping Mission di Lebanon sebagai Implementasi Diplomasi Pertahanan - Khoirunnisa, Tsabita Afifah; Jannah, R. AJ. Feyfil; Qonita, Mafazati; Tjondrodewi, Dena Caristy (Department of International Relations, Brawijaya University, 2022)
ABSTRACT This study aims to find out more about how the conditions in Lebanon lead Indonesia to uphold peace by mobilizing its energy in peacekeeping operations. This study shows how Indonesia has participated in participating together with the peace organization UNIFIL (United Nations Interim Force in Lebanon) in carrying out its free-active politics by sending the Garuda Contingent (KONGA) to several conflict areas in Lebanon. Indonesia's participation in this program is a manifestation of its foreign policy in the form of defence diplomacy, further this research discusses how the contingent sent by Indonesia became one of Indonesia's defence diplomacy. Defence diplomacy is one of the defence strategies that refers to ends, means, and ways that can give birth to several policies taken by Indonesia in which Indonesian defence diplomacy is a form of soft diplomacy which is one way to achieve a country's national interest. Keywords: Defence Diplomacy, Indonesia, Peacekeeping Operations, Confidence-Building Measure